Digital realities in education: projects implemented using augmented reality in Portugal - Rito, P. N. (2022)
The use of mobile devices by students and teachers in the classroom has been widely discussed in the literature. In addition to the traditional access to specific web pages, there are reports about the use of applications that allow access to complex information like animations, videos, and three-dimensional objects. That, in some cases, can be previously planned by the educator, or the educator uses specific applications that already exist on the market. To help educators in this process, they have tools at their disposal to use augmented reality in classroom contexts. The use of this technology has another advantage that has already been identified in the literature: it is an appealing way to focus the attention and interest of its users. An open repository in Portugal (RCAAP) allows access to a wide range of publications (articles, theses, and other scientific documents) that were written or that had the collaboration of professors or researchers from higher education institutions or belonging to an investigation. Despite the limitations of this repository, it is possible to access a set of documents that reveal the state of the art of what has been produced at the scientific level in Portugal. In the research that we carried out through the RCAAP on May 31, it was possible to verify that there are cases of educators who make use of applications that exist in the market to implement the use of digital realities in the classroom context and in these cases, there is no need to program applications. It was also possible to verify the possibility of adapting existing applications to different educational contexts and levels of education. These and other information are important and help to reflect on the topic of digital realities. This investigation uses a systematic review work that aims to understand: the contexts in which applications have been used, answer the question about which applications have been used, what are their characteristics, and then obtain a data reference that will serve as a basis for the design, development, and implementation of an application based on the use of augmented reality.